A Theoretical Review on Factors of Working Capital Management - Upreti, Dharma Raj; Kulshrestha, Sweta (Nepal Journal of Multidisciplinary Research, 2022)
Working capital management is detected internally by organization specific factors such as size, age, profitability, growth in revenue, market share, operating risk and operating cash flow. Similarly, it is externally detected by macroeconomic factors such as Gross Domestic Product, Rate of interest rate and rate of taxes. Impressive and well-regulated working capital management has a notable out-turns on the success or the failure of any business organization in the short-run or long-run as it strikes the liquidity and profitability parity of a business organization. The success of any organization undoubtedly is conditional on how effectively financial managers manage working capital elements such as cash, receivables, inventories and payables. It is a must for a business organization to perpetuate symmetry between liquidity and profitability in conducting its daily operations. In this regard, this very article tries an utter on the factors of working capital management.